Propagação vegetativa de crateva benthamii com diferentes concentrações de ana - Silva , Ângela Alves da (2004)
Crateva benthamii Eichler (Capparaceae) is a typical floodplain forest species with high economic potential on pisciculture, pharmacological industry and environment recuperation in degraded areas. This work assessed the C. benthamii propagation in different ANA concentration and the kind of stake. The experiment was installed in the INPA warren V8 (Manaus-AM, Brazil). It was utilized delineation of casual blocks with five repetitions, with 3 x 4 factorial scheme, in which the factors comprehended the kinds of stake (apex, middle and base) and ANA concentration (0, 100, 1.000 and 10.000ppm). The bases of the stakes were plunged into ANA aqueous solutions during 24 hours. The evaluated parameters were: percentage of survival, percentage on rooting and cuttings having shoots and roots. After 90 days of planting, the apex cuttings showed lesser percentage on survival with 100% of mortality in 10.000ppm treatment. Between middle stakes and base stakes there was no statistical difference, showing higher indices on survival (70% and 80%, respectively). The higher percentage of rooting was in 1.000ppm concentration (70%), there was no statistical difference when compared with stakes any hormone treatment and stakes with 100ppm. The middle stakes and base stakes showed the highest percentages of shoot protrusion at 90 days (38,75% and 36,25%). There was statistical difference when compared with apex stakes (17,50%). The middle stakes and the base stakes of C. benthamii showed the highest percentage of survival. The variation concentration about ANA tested did not favor the rooting. C. benthamii shows higher potential for propagation per cutting and can be an option to recuperate degraded areas in floodplain forest.